Temporal variation of Malaysian rotavirus electropherotypes. - Rasool, N.; Othman, R.Y.; Adenan, M.I.; Hamzah, M. (American Society for Microbiology, 1989)
An analysis of rotavirus electropherotypes circulating in Kuala Lumpur, Malaysia, over 7 years showed that all except 1 of the 360 electropherotypes encountered were characteristic of group A rotaviruses. The long electropherotype predominated annually, and there was a rarity of short electropherotypes. Extensive genome variability and cocirculation of different electropherotypes were observed annually. A sequential appearance of the predominant electropherotype was observed in all years of the study, except for 1985 and 1988, when one electropherotype predominated throughout the study periods. There was no shift in the predominant electropherotype over a 6-year period.